Translation of the Prayer of Manasseh found in the Six-Volume Kralice Bible - Dittmann, Robert (Bohemica Olomucensia, 2013)
The contribution deals with the Czech translation of the Prayer of Manasseh found in the Six-Volume Kralice Bible. Comparing the Czech version with the alleged Latin Vorlage in the Antwerp Polyglot, the author tries to demonstrate that numerous textual deviations point to different sources as the main textual models for the translation, namely the Latin translation appearing in the Tremellius-Junius Old Testament version and some other humanistic translations.